Psychological methods of pain control : basic science and clinical and perspectives - Price, Donald D; Bushnell, M. Catherine (IASP Press, 2004)
The International Association for the Study of Pain (IASP) regards pain as a multidimensional phenomenon. Prefatory remarks note that recent developments have greatly expanded understanding of the neural bases of the placebo effect, attention, expectation, emotions, suggestions and hypnosis on pain perception. Price (neuroscience, oral and maxillofacial surgery, U. of Florida) and Bushnell (anesthesia, dentistry, McGill U.) introduce the psychological and neurophysiological processing of pain and general mechanisms of pain modulation. International experts treat specific pain reduction mechanisms. Brain scans illustrate how psychological factors mediate imaged activity indicative of pain sensation. Annotation © 2004 Book News, Inc., Portland, OR Editorial Reviews Reviewer: Jeffrey L Apfelbaum, M.D.(University of Chicago Pritzker School of Medicine) Description: This book, volume 29 in the Progress in Pain Research and Management series, addresses both clinical perspectives and basic science perspectives in an up-to-date analysis of the psychological methods of pain control. The producer of this series, the International Association for the Study of Pain (IASP), is devoted to understanding the mechanisms of pain and improving the care of patients with pain through research, education, and communication; organizational membership includes scientists and healthcare professionals dedicated to achieving the aforementioned goals. Purpose: The editors note that the past decade has seen remarkable developments in studies of psychological factors that influence pain, including but not limited to, attention, emotions, and suggestions. They also note that there have been marked improvements in psychological methods of pain management such as hypnosis, although these developments have drawn much skepticism, particularly with regard to the role of such psychological influences on pain.
Progress in pain research and management ; vol. 29
Keywords: psychologie, klinická psychologie; psychosomatické lékařství; bolest; Pain; analgezie; Analgesia; Psychosomatic Medicine